Against zetetic encroachment - Vollmer, Michael (Synthese, 2024)
Proponents of zetetic encroachment claim that certain zetetic or inquiry-related considerations can have a bearing on the epistemic rationality of one’s belief formation. Since facts about the interestingness or importance of a topic can be the right kind of reasons for inquisitive attitudes, such as curiosity, and inquisitive attitudes are ways to suspend judgement, these facts also amount to reasons against believing. This mechanism is said to explain several contentious phenomena in epistemology, such as the occurrence of pragmatic encroachment. In this paper, I provide two lines of reasoning against zetetic encroachment. First, on any contrastivist understanding of epistemic reasons, the case in favour of zetetic encroachment loses all its motivational force. Second, the thesis of zetetic encroachment is incompatible with the most promising way to understand degrees of inquisitive attitudes.
Gesehen am 09.12.2024